Organisational behaviour and analysis - Rollinson, Derek (Prentice Hall, 2005)
A comprehensive introduction to Organisational Behaviour and Analysis with a distinctive psychological outlook. Avoiding a managerialist approach, the book places emphasis on Organisational Behaviour & Organisational Analysis as 'neutral' subjects concerned with understanding, rather than controlling, human behaviour in organisations. Aimed at students taking an introductory course in Organisational Behaviour on undergraduate and postgraduate degree programmes, or as part of a professional qualification. A wide range of cases and examples -- many taken from the Financial Times -- exercises and discussion questions encourage critical reflection on both theory and practice. A supporting website (www.pearsoned.co.uk/rollinson) provides a longer case study for each chapter, interactive questions for self-assessment, and suggestions for further reading and research.